2020
DOI: 10.1177/2040620720910964
|View full text |Cite
|
Sign up to set email alerts
|

Management of Epstein–Barr virus-related post-transplant lymphoproliferative disorder after allogeneic hematopoietic stem cell transplantation

Abstract: Epstein–Barr virus-related post-transplant lymphoproliferative disorder (EBV-PTLD) is a rare but life-threatening complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). T-cell immunodeficiency after transplantation and EBV primary infection/reactivation play major roles in the pathogenesis. Unspecific clinical manifestations make the diagnosis difficult and time consuming. Moreover, this fatal disease usually progresses rapidly, and leads to multiple organ dysfunction or death if no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
(206 reference statements)
0
11
0
Order By: Relevance
“…Most patients had a history of organ transplantation, immunosuppression, and immune deficiency, and EBER positivity was detected in tumor cells. Studies have shown that transplantation, immunosuppression, and immune deficiency can induce primary infection or reactivation of EBV ( 19 , 20 ). However, among the 382 cases of FL reported by Mackrides et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients had a history of organ transplantation, immunosuppression, and immune deficiency, and EBER positivity was detected in tumor cells. Studies have shown that transplantation, immunosuppression, and immune deficiency can induce primary infection or reactivation of EBV ( 19 , 20 ). However, among the 382 cases of FL reported by Mackrides et al.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, delta-2+ lymphocytes proved to be cytotoxic against EBV infected cells ( 98 ); in another study, delta-2+ recovery seemed to exert a protective role from EBV reactivation ( 99 ). The same authors showed that mycophenolate-driven inhibition of delta-2+ gamma-delta lymphocytes could play a role in the pathogenesis of PTLD, at least in the haploidentical setting ( 100 ).…”
Section: Management Of Viral Infections After Hsctmentioning
confidence: 99%
“…Reduction of immunosuppression (RI) as tolerated is a cornerstone to restore EBV-directed immunity; however, it must be balanced against the risk of graft-versus-hostdisease (GvHD) or organ graft rejection (5,11). Treatment with rituximab, a chimeric monoclonal antibody (mAb), with or without chemotherapy is currently accepted as the first-line choice for preemptive intervention and targeted treatment (12) in a broad variety of CD20 + B-cell malignancies, including EBV-positive lymphomas. For EBV-associated PTLD, rituximab treatment resulted in complete remission in more than 60% of patients (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%